Associations between DNA methylation and telomere length during early life: Insight from wild zebra finches (Taeniopygia guttata). Issue 23 (5th October 2021) - Sheldon, Elizabeth L.; Ton, Riccardo; Boner, Winnie; Monaghan, Pat; Raveh, Shirley; Schrey, Aaron W.; Griffith, Simon C.
Abstract: Telomere length and DNA methylation (DNAm) are two promising biomarkers of biological age. Environmental factors and life history traits are known to affect variation in both these biomarkers, especially during early life, yet surprisingly little is known about their reciprocal association, especially in natural populations. Here, we explore how variation in DNAm, growth rate, and early‐life conditions are associated with telomere length changes during development. We tested these associations by collecting data from wild, nestling zebra finches in the Australian desert. We found that increases in the level of DNAm were negatively correlated with telomere length changes across early life. We also confirm previously documented effects of post hatch growth rate and clutch size on telomere length in a natural ecological context for a species that has been extensively studied in the laboratory. However, we did not detect any effect of ambient temperature during developmental on telomere length dynamics. We also found that the absolute telomere length of wild zebra finches, measured using the in‐gel TRF method, was similar to that of captive birds. Our findings highlight exciting new opportunities to link and disentangle potential relationships between DNA based biomarkers of ageing, and of physiological reactions to environmental change.